Developing a solar calculator system - Muhammad-Sukki, Saidalmaruzi; Mohd Niyaz Khan, Mohd Toriq Khan; Zeki, Akram M.; Abubakar, Adamu; Muhammad-Sukki, Firdaus (Trans Tech Publications, Switzerland, 2014)
There is a rapid increase in global warming over the years. This follows with continues campaign on reducing the energy consumption and protecting the earth against climate change. The Feed-In Tariff (FiT) program was introduced to encourage people to use renewable energy. One of the alternative energies that has shown significant potential is solar energy, which could be harvested using the solar photovoltaic (PV) technology. This project is intended in developing an online application system to help the user in making a decision about installing a solar PV system. This system will help the user to calculate the size of solar panel that a user should install, the amount of electricity generated from the system and the profit that the user will gain after a few years in implement solar PV system in his premise(s) or house(s).